2008
DOI: 10.1143/jjap.47.7459
|View full text |Cite
|
Sign up to set email alerts
|

Nanopore Size Estimation by Electrochemical Impedance Spectroscopy Analysis

Abstract: We present a simple and cost-effective approach by electrochemical impedance spectroscopy (EIS) for the accurate pore size estimation of silicon based nanopores. This method takes into account the capacitor effects of the electrical double layer and the resistor effects of the ion concentration inside the nanochannel. The nanopore impedance was modeled as the electrolyte resistance R s in series with a parallel ion diffusion circuit charge transfer resistance R f with a constant phase element (CPE) that models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…However, the fluorescent probe molecules may have an effect on the water properties. Other groups performed the electrical impedance measurement of liquids in nanopores using an alternate current (ac) method. , In these experiments, a voltage was applied to the nanopores using bulk electrodes. However, using this arrangement, signals were obtained from liquids in the nanopores and in the bulk and from the nanopore and electrode materials.…”
mentioning
confidence: 99%
“…However, the fluorescent probe molecules may have an effect on the water properties. Other groups performed the electrical impedance measurement of liquids in nanopores using an alternate current (ac) method. , In these experiments, a voltage was applied to the nanopores using bulk electrodes. However, using this arrangement, signals were obtained from liquids in the nanopores and in the bulk and from the nanopore and electrode materials.…”
mentioning
confidence: 99%
“…R p and R s show opposite trends and explained as the effect of pore structure parameters of the electrodes on their respective internal resistance per unit electrode geometric area . Available electrolyte ions inside the pores generates an electrical double layer on inner surface of pores which resulted in high impedance inside the pores thus, R p is much larger than R s …”
Section: Resultsmentioning
confidence: 98%
“…Therefore, R P is much larger than R S . It is also found that both R S and R P decrease with increasing concentration indicating that the nanopore resistance is a function of the electrolyte concentration inside the nanopore, so the high concentration ratio induced by the trans-membrane potential increases the mobility of the charged ions inside the nanopore resulting in a relatively lower electrolyte resistance [ 38 ].…”
Section: Resultsmentioning
confidence: 99%